Measuring the impact of customer satisfaction on business profitability: an empirical study. (11th September 2019) - Drosos, Dimitris; Skordoulis, Michalis; Chalikias, Miltiadis
According to many studies customer satisfaction is strongly correlated with business profitability. Thus, customer satisfaction has gained scholars' interest worldwide. Business profitability can derive from customer loyalty and an increasing market share. This paper aims to shed some light on the relationship between business profitability and customer satisfaction. Customer satisfaction data were collected from 6, 968 mobile communications customers from Greece. Customer satisfaction was measured using the MUSA method, a multi-criteria analysis based on the principles of qualitative regression. The relationship between customer satisfaction and business profitability results has been analysed using correlation coefficients and regression models. The findings support a positive correlation between customer satisfaction and the constructs of business profitability.